49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-1079
|View full text |Cite
|
Sign up to set email alerts
|

Flow Separation Control on Airfoil With Pulsed Nanosecond Discharge Actuator

Abstract: An experimental study of flow separation control with a nanosecond pulse plasma actuator was performed in wind-tunnel experiments. The discharge used had a pulse width of 12 ns and rising time of 3 ns with voltage up to 12 kV. Repetition frequency was adjustable up to 10 kHz. The first series of experiments was to measure integral effects of the actuator on lift and drag. Three different airfoil models were used, NACA-0015 with the chord of 20 cm, NLF-MOD22A with the chord of 60 cm and NACA 63-618 with the cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 2 publications
1
37
0
1
Order By: Relevance
“…In other words, flow forcing in LAFPA and nanosecond pulse DBD actuators may well occur on the same time scale, and the mechanisms of flow control for both types of actuators may be similar. Indeed, large-scale structures (spanwise vortices) detected in recent studies of high-speed airfoil flow control using nanosecond pulse DBD plasma actuators [11][12][13][14] are similar to those detected in experiments using LAFPA actuators in jet flows.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In other words, flow forcing in LAFPA and nanosecond pulse DBD actuators may well occur on the same time scale, and the mechanisms of flow control for both types of actuators may be similar. Indeed, large-scale structures (spanwise vortices) detected in recent studies of high-speed airfoil flow control using nanosecond pulse DBD plasma actuators [11][12][13][14] are similar to those detected in experiments using LAFPA actuators in jet flows.…”
Section: Introductionmentioning
confidence: 53%
“…2). This effect results in flow reattachment over a wide range of discharge pulse repetition rates [11][12][13][14]. Also, compression waves generated in a NS-DBD actuator placed on the surface of a cylinder model in a Mach 5 flow were demonstrated to strongly perturb the bow shock in front of the model, which increased the shock stand-off distance, as shown in Fig.…”
Section: Introductionmentioning
confidence: 80%
“…The shock wave generated by actuators can be clearly seen, as well as large scale vortex structure as it developed 40 microseconds after the discharge [Correale et al, 2011]. It was observed that after 2-3 discharges the flow pattern changed completely.…”
Section: Boundary Layer Separation Control By Heat Releasementioning
confidence: 70%
“…Numerical modeling of SDBD development also shows fast formation of plasma layer and shock wave generation [Unfer&Boeuf, 2009;Starikovskii et al, 2009]. The process of nanosecond pulsed plasma layer interaction with the flow, formation of perturbations and vortices, and flow re-attachment was investigated in details in [Correale et al, 2011]. A model of NACA 63-618 airfoil with the chord of 20 cm and span of 40 cm with the actuator applied was used for experiments.…”
Section: Boundary Layer Separation Control By Heat Releasementioning
confidence: 99%
See 1 more Smart Citation